Accounting measurement of Balance Sheet items according to the financial accounting system - Zine, Abdelmalek (Finance and Business Economies Review, 2022)
The primary objective of this study is to highlight the reality of the accounting measurement of budget items in the light of the implementation of the financial accounting system, in addition to illustrating the extent to which this measurement contributes to preparing and providing a clear picture of the institution's situation by offering credible and decision-making-capable information. A descriptive-analytical research method is used to achieve the research objectives. The results indicated that the Algerian telecom direction of Khenchela city depends mainly on the historical cost of measuring the budget elements, which makes the accounting value of this society differ from the market value of its parts, and consequently negatively affects the users of accounting information.